Autoinscrever(-se): narrativas de uma professora e estudantes pretas - Bruna Vasconcelos de Santana (2024)
This study presents a reflection on the absence of Black Brazilian Literature in the intellectual, historical and social formation of the teacher, the author of this study, and of 10 9th grade students, all black women and teenagers, at the Jesus Cristo School, where the teacher works and the students study. At this institution, experiences with Black Brazilian Literature were developed, due to the recognition that there is still exclusion and silencing, in the educational process, regarding texts written by black people, especially authors. The importance of these references in the process of constructing the identities of the people who make up the study is recognized. In this investigation, we sought to find ways to transform this scenario through contact with some of these textual genres and the creation of self-narratives. The act of writing emerges as an opportunity to self-inscribe ourselves, as black women and teenagers. In this sense, works by authors Carolina Maria de Jesus, with the book Quarto de despejo: diário de uma favelada, and Conceição Evaristo, with Olhos D’água, were triggers for the pedagogical product of this research, which consisted of 8 meetings, entitled Tessituras de Fios. The methodological approach of this research was autoethnographic, as this approach allows for an inside-out look, focused on the participants’ experiences, composing meanings, interpretations and autonomy in writing. In addition, it also had a collaborative character, understanding that collectivity generates the emancipation of the people involved in the research, as well as the use of school ethnography, through the constant movement from practice to theory and a return to practice to transform it. There was also the use of cartography, which allows for establishing bridges in the dynamics of the path, through records, recognition of identifications, the possibility of perceiving the unique and revealed in the encounters and disagreements of the process, as it happens. Finally, writing was used as a writing method. Thus, the research revealed that Brazilian Black Literature in the historical, political and social formation of black women and adolescents represents an act of identity resistance. This action fosters changes in attitude based on collective learning and self-narrative experiences, composing the “writing experience” about the concerns of our lives as black women and adolescents.